2018
DOI: 10.1002/jmri.26587
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI contribute to pulmonary nodule analysis?

Abstract: Background There is no accurate method distinguishing different types of pulmonary nodules. Purpose To investigate whether multiparametric 3T MRI biomarkers can distinguish malignant from benign pulmonary nodules, differentiate different types of neoplasms, and compare MRI‐derived measurements with values from commonly used noninvasive imaging modalities. Study Type Prospective. Subjects Sixty‐eight adults with pulmonary nodules undergoing resection. Sequences Respiratory triggered diffusion‐weighted imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Jiang et al ( 41 ) suggested that the nodule with a diameter smaller than 2 cm or a lower lung zone location would negatively affect the reproducibility. In addition, Koo et al ( 42 ) found that most nodules (74%) in their study were <2 cm, and nearly half of the lesions were in the lower lobes. The “3.0 T” MRI scanner showed a higher sensitivity for ADC than the “1.5 T” MRI scanner.…”
Section: Discussionmentioning
confidence: 81%
“…Jiang et al ( 41 ) suggested that the nodule with a diameter smaller than 2 cm or a lower lung zone location would negatively affect the reproducibility. In addition, Koo et al ( 42 ) found that most nodules (74%) in their study were <2 cm, and nearly half of the lesions were in the lower lobes. The “3.0 T” MRI scanner showed a higher sensitivity for ADC than the “1.5 T” MRI scanner.…”
Section: Discussionmentioning
confidence: 81%
“…A total of 6 patients could not be included in the final analysis, with only two not being able to be examined due to their poor general condition. T1 and T2 values normalized to muscles correlated significantly with the standard uptake values (SUV) from PET/CT images in a study by Koo et al that considered the differentiation of benign and malignant nodules [20]. In another study by Li et al, the qualitative assessment of the T1 and T2 signal intensity of nodules in relation to muscle and fat was used in the follow-up after cryoablation of lung tumors [21].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have already demonstrated the value of analyzing radiomic features in CT and MRI datasets in evaluating pulmonary nodules [ 27 , 28 , 29 , 30 , 31 , 32 ]. This study is the first to show that by combining quantitative image information from CT, T2w, and DWI datasets in a backward selection process, assessing pulmonary nodules through radiomics analysis is superior to that of one modality alone, even exceeding human readers’ performance.…”
Section: Discussionmentioning
confidence: 99%